Ethyl 2-amino-4-(3-chlorophenyl)-5,10-dioxo-5,10-dihydro-4H-benzo[g]chromene-3-carboxylate - Hu, Xiao (International Union of Crystallography, 2009)
The title molecule, C(22)H(16)ClNO(5), was obtained by the reaction of (E)-ethyl 3-(3-chlorophenyl)-2-cyanoacrylate and 2-hydroxynaphthalene-1,4-dione catalysed by triethylamine in ethanol. In the crystal structure, the chlorobenzene ring makes a dihedral angle of 88.63 (4)° with the fused ring system. The six-membered ring formed by an intramolecular N—H⋯O hydrogen bond is almost planar. The crystal packing is stabilized by N—H⋯O hydrogen bonds.